Analyzing the Relationship between Financial Inclusion, Savings Behavior, and Standard of Living in Low-Income Households in Africa - Nambie, Nicholas Bamegne; Ocansey, Evans O. N. D; Ababio, Opoku K. (Archives of Business Research, 2025)
Using quantitative research approaches and data from the World Bank Development Indicators (WDI) and the International Monetary Fund, this study examines the relationship between financial inclusion, savings behavior, and the standard of living in low-income households in Africa over the period 2003 to 2024. The paper investigates how standard of living is affected by financial inclusion and savings behavior using Ordinary Least Squares, Random Effects Models, and Structural Equation Modeling. The results show that financial inclusion influences savings behavior, which raises the quality of standard of living by itself. More specifically, access to financial services helps people participate in official savings, therefore increasing their capacity to invest in income-generating activities, health, education, and other areas. Policy ramifications include for more financial access, encouragement of financial literacy, and the development of custom financial solutions for low-income groups. Among the recommendations are using digital finance, including financial inclusion into national development agendas, and correcting gender gaps. Future studies should look at gender-specific effects, behavioral elements affecting saves, and the part digital finance plays in encouraging financial resilience among low-income families.